Prespektif Ekonomi Islam: Saluran, Kendala Dan Pendapatan Dalam Tata Niaga Udang Vanname - Adzil Arsyi Sabana (Robust: Research of Business and Economics Studies, 2023)
AbstractThis research aims to analyze the shrimp supply chain in Muara Lapao-Pao Village, Wolo District, Kolaka Regency, with a focus on the challenges faced and the income levels of shrimp farmers from the perspective of Islamic economics. Using a qualitative approach and field research methods, this study identifies three main marketing channels involving shrimp farmers, traders, collectors, retailers, and consumers. The research findings indicate that the vannamei shrimp farming industry in this area has seen a steady increase in income over the years, providing livelihoods for the local community and applying Islamic marketing principles such as unity, permissibility, justice, free will, and willingness, with a focus on benefit and customer satisfaction.AbstrakPenelitian ini bertujuan untuk menganalisis saluran tata niaga udang di Desa Muara Lapao-Pao, Kecamatan Wolo, Kabupaten Kolaka, dengan fokus pada kendala-kendala yang dihadapi dan tingkat pendapatan petambak dalam perspektif ekonomi Islam. Melalui pendekatan kualitatif dan metode penelitian lapangan, penelitian ini mengidentifikasi tiga saluran pemasaran utama yang melibatkan petambak, pedagang, pengumpul, pengecer, dan konsumen. Hasil penelitian menunjukkan bahwa usaha tambak udang vanname di daerah ini mengalami peningkatan pendapatan dari tahun ke tahun, memberikan mata pencaharian bagi masyarakat setempat, dan menerapkan prinsip-prinsip pemasaran Islam seperti kesatuan, kebolehan, keadilan, kehendak bebas, dan kerelaan dengan fokus pada kemaslahatan dan kepuasan pelanggan.